2020
DOI: 10.1021/acsbiomaterials.0c00942
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Stromal Cell Patch Integrated with Engineered Microvessels Improves Recovery from Myocardial Infarction in Rats and Pigs

Abstract: The vascularized cardiac patch strategy is promising for ischemic heart repair after myocardial infarction (MI), but current fabrication processes are quite complicated. Vascularized cardiac patches that can promote concurrent restoration of both the myocardium and vasculature at the injured site in a large animal model remain elusive. The safety and therapeutic benefits of a cardiac stromal cell patch integrated with engineered biomimetic microvessels (BMVs) were determined for treating MI. By leveraging a mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…The cellular patches are generated through seeding of different live cells into various 3D scaffolds. To enhance the survival of the transplanted live cells, the patches have been engineered with mimetic blood vessels ( Su et al, 2018a , 2020 ) or cocultured with ECs ( Shadrin et al, 2017 ). For better integration, the scaffold has been engineered with microneedles ( Tang et al, 2018b ).…”
Section: Discussionmentioning
confidence: 99%
“…The cellular patches are generated through seeding of different live cells into various 3D scaffolds. To enhance the survival of the transplanted live cells, the patches have been engineered with mimetic blood vessels ( Su et al, 2018a , 2020 ) or cocultured with ECs ( Shadrin et al, 2017 ). For better integration, the scaffold has been engineered with microneedles ( Tang et al, 2018b ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, apart from exosomes, some other cell‐based therapeutic approaches have been investigated. For example, it has been reported that the pre‐vascularized cardiac stromal cell patch generated from therapeutic cardiosphere‐derived stromal cells integrated with engineered micro‐vessels evidently improved the process of recovery from myocardial infarction in animal models 30,31 . Moreover, other methods including bispecific antibody inhalation therapy, platelet‐inspired nanocell injection and nanogel‐encapsulated human cardiac stem cell injection were also reported 32‐35 …”
Section: Discussionmentioning
confidence: 99%
“…156 Pre-vascularization of cardiac patches has been proposed as a promising strategy allowing the fabrication of thicker patches without compromising cell viability. For instance, Su et al 157 encapsulated microengineered endothelialized microvessels with an inner and outer diameter of approximately 250 and 550 μm, respectively, in a fibrin gel containing therapeutic cardiospherederived stromal cells (CSCs). The resulting patch released paracrine factors in a sustained manner with levels comparable to that produced during the co-culture of human CSCs and human umbilical vein endothelial cells (HUVECs).…”
Section: Thickness Of Cardiac Patchesmentioning
confidence: 99%